2016
DOI: 10.1038/nature20591
|View full text |Cite
|
Sign up to set email alerts
|

Chemical intervention in plant sugar signalling increases yield and resilience

Abstract: The pressing global issue of food insecurity due to population growth, diminishing land and variable climate can only be addressed in agriculture by improving both maximum crop yield potential and resilience. Genetic modification is one potential solution, but has yet to achieve worldwide acceptance, particularly for crops such as wheat. Trehalose-6-phosphate (T6P), a central sugar signal in plants, regulates sucrose use and allocation, underpinning crop growth and development. Here we show that application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(166 citation statements)
references
References 41 publications
7
156
0
3
Order By: Relevance
“…Using an elegant chemical approach, it was recently shown that T6P can directly promote grain filling in wheat (Triticum aestivum). Spraying of wheat plants with compounds that release T6P upon exposure to sunlight led to increased grain yield due to the formation of larger grains with higher starch content (Griffiths et al, 2016b). Earlier work had shown that T6P naturally accumulates in wheat grains to previously unreported levels before grain filling (Martínez-Barajas et al, 2011).…”
Section: Seed Developmentmentioning
confidence: 99%
“…Using an elegant chemical approach, it was recently shown that T6P can directly promote grain filling in wheat (Triticum aestivum). Spraying of wheat plants with compounds that release T6P upon exposure to sunlight led to increased grain yield due to the formation of larger grains with higher starch content (Griffiths et al, 2016b). Earlier work had shown that T6P naturally accumulates in wheat grains to previously unreported levels before grain filling (Martínez-Barajas et al, 2011).…”
Section: Seed Developmentmentioning
confidence: 99%
“…T6P-inhibited SnRK1 will up-regulate carbohydrate storage, prime gene expression for growth, growth recovery and signals satiety, whereas uninhibited SnRK1 will signal starvation, catabolism and will slow growth. Indeed, the T6P:SnRK1 relationship is considered a major player in directing carbohydrates between source and sink tissues, and can be a key factor in the survival of environmental stress [116][117][118][119]. This has been addressed in Arabidopsis, where accumulated T6P under sink-limited stress conditions inhibits SnRK1 activity, and thus allows synthesis and growth to resume rapidly once the growth limiting stress conditions were alleviated [118].…”
Section: The Role Of Trehalose-6-phospate In Desiccation Tolerancementioning
confidence: 99%
“…It was discovered in plants rather late, and it was thought that it could act in plant tissues only as an osmoprotectant under drought conditions [44]. In the last decade, trehalose-6-P was found to be essential for the normal growth and development of plants and for stable sugar metabolism [25,45,[92][93][94]. Many genes encoding Tre6P synthase and phosphatase in plants have been discovered, however, not all of their products are catalytically active [25,44].…”
Section: Receiving and Transmitting The Signals Triggered By Sugarsmentioning
confidence: 99%
“…However, lately, a model has been proposed with Tre6P as an essential factor, connecting sugars with plant growth and development [8,24,48,91,92]. The effects of Tre6P on the different stages of plant development and interaction with sugar and mediators of sugar signaling were recently discussed in detail [7,24,48,[91][92][93][94].…”
Section: Receiving and Transmitting The Signals Triggered By Sugarsmentioning
confidence: 99%